Peningkatan Excess Spending Pada Platform E-Commerce Dengan Pendekatan Persepsi Bookkeeping Account - Haryana, Ratih Dewi Titisari (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2025)
Technological developments and easy access to e-commerce platforms have driven significant changes in people's consumption patterns. This study was conducted based on individual behavior that often unconsciously applies accounting principles in their lives, especially in terms of financial management. Bookkeeping account is a term where each individual uses bookkeeping accounts like financial reports in managing their finances. Bookkeeping account is based on the framing effect where this is the effect of a person's cognitive bias behavior in decision making. In addition to the framing effect, there is also cash flow of personal funds and savings where these indicators are predicted to influence the attitude of excess spending in individuals, especially online shopping through various e-commerce platforms in the current digitalization era. Quantitative research methods were chosen to solve the problem formulation in this study. The selected research sample focused on productive-aged women who were considered to shop online more often, in the cities of Surabaya and Sidoarjo (the selection of areas was based on population density in East Java) so the sampling method used is cluster sampling. The questionnaire was sent directly or via GForm media to collect data. The data analysis method used partial Least Squares and structural equation model methodology. The results of the study show that the framing effect and cash flow of personal funds are able to provide a significant influence on excess spending, while saving is not able to significantly influence excess spending behavior in each individual.